The house we grew up in ebook A novel. - Jewell, Lisa (2014)
From the New York Times bestselling author of None of This Is True and Then She Was Gone comes an unforgettable saga that follows the Bird family and how one tragedy ripples throughout their lives for years. Meet the picture-perfect Bird family: pragmatic Meg, dreamy Beth, and towheaded twins Rory and Rhys, one an adventurous troublemaker, the other his slighter, more sensitive counterpart. Their father is a sweet, gangly man, but it's their beautiful, free-spirited mother Lorelei who spins at the center. In those early years, Lorelei tries to freeze time by filling their simple brick house with precious mementos. Easter egg foils are her favorite. Craft supplies, too. She hangs all of the children's art, to her husband's chagrin. Then one Easter weekend, a tragedy so devastating occurs that, almost imperceptibly, it begins to tear the family apart. Years pass and the children have become adults, while Lorelei has become the county's worst hoarder. She has alienated her husband and children and has been living as a recluse. But then something happens that beckons the Bird family back to the house they grew up in—to finally understand the events of that long-ago Easter weekend and to unearth the many secrets hidden within the nooks and crannies of home.